KOMUNITAS PENULIS ILMIAH (KOPI); UPAYA PENINGKATAN DAYA SAING MAHASISWA MELALUI PELATIHAN KETERAMPILAN MENULIS - Nasrul Hakim; Dwi Kurnia Hayati; Hifni Septina Carolina; Tri Andri Setiawan; Tika Mayang Sari; Asih Fitriana Dewi; Pundi Restu Lulul Hakiki; Siti Soleha (JPM: Jurnal Pengabdian Masyarakat, 2021)
This community service activity aims to provide assistance to FTIK IAIN Metro students in terms of writing, providing training with various materials about scientific writing, assisting, providing motivation and providing directions as well as various information on competitions, seminars and scientific journal publications. The result of this activity is in the form of increased motivation and writing skills of students participating in the scientific writing community (KOPI). This result is marked by the achievement of student achievements in various scientific writing competitions, the publication of student writings in various accredited national scientific journals, passing as a speaker at various national seminars, published in various local mass media and several books with ISBN. This service activity is expected to continue to be developed with a wider scope as an effort to increase the competitiveness of students and institutions at large.